The mediating role of health literacy between the presence of chronic disease and psychological distress among older persons in Xian City of China - Guo, Kun; Ouyang, Jing; Minhat, Halimatus Sakdiah (Springer Science and Business Media, 2023)
Background: The increased number of older persons in China, and the prevalence of most chronic diseases raised with age significantly increased the total disease burden. When a person ages, psychological distress happens when they are faced with stressors that they cannot cope with. Psychological distress refers to non-specific symptoms of depression, anxiety, and stress. Health literacy influences several health outcomes, such as emotional functioning among the population. The primary purpose of this study is to examine the mediator role of health literacy between the presence of chronic disease and psychological distress among older persons living in Xi’an city. Thus, this study used the Cognitive Behavior Theory (CBT) as a combination of the basic behavioral and cognitive psychology principles to explain the cognitive processes associated with psychological distress.